A review on the activities and questions related to text type and structure in the secondary school Turkish textbooks - Erhan Şen (Elementary Education Online, 2023)
In this study, activities and questions connected to text type and structure in Turkish textbooks of secondary schools were examined. In this descriptive qualitative study, content analysis method is used to examine the data. It was found that activities and questions in the secondary school 5th-8th-grade Turkish textbooks that are published and approved by the Ministry of National Education in the 2018- 2019 academic year were not balanced or systematic in terms of numerical and class levels. It is determined that students are intensively introduced with informational text types. In terms of frequency, it was determined that narrative texts were second, poetry was third. It is observed that the structure of informational texts is not adequately focused in terms of structural components. The elements of the narrative texts have been taken more places in terms of frequency. In this respect, it is difficult to mention a parallel between the types of texts discussed and the structural or types of components that are taken into consideration. Hence, it can be said that activities related to the structure of informational texts in textbooks remain superficial.